Faktor yang Mempengaruhi Kepatuhan Konsumsi Tablet Tambah Darah Siswa SMPN 1 Tanah Luas - Raudatul Asyikin; Hafni Zahara; Futry Maysura (Lembaga Pengembangan Kinerja Dosen, 2026)
Among adolescents, especially female students currently studying, anemia remains a health problem that requires attention. Therefore, this study aims to analyze various factors that influence the adherence of students at SMPN 1 Tanah Luas, Tanah Luas District, North Aceh Regency, to iron supplementation tablets, using a quantitative cross-sectional design. The sample used was 40 students selected through a purposive sampling method. The independent variables were peer influence and family support, while the dependent variable was iron supplementation compliance. Data were collected using a questionnaire that had passed validity tests and analyzed using multiple linear regression techniques using SPSS version 25. The results indicated that family support was a significant factor in student adherence, while peer influence did not show a statistically significant relationship. The regression model accounted for 53.4% ​​of the variation in adherence. This study concluded that family support is a factor that significantly influences iron supplementation habits among adolescents. Family involvement is recommended in initiatives aimed at improving iron supplementation compliance.